2015
DOI: 10.3758/s13414-015-0943-0
|View full text |Cite
|
Sign up to set email alerts
|

Attentional cartography: mapping the distribution of attention across time and space

Abstract: Decades of research have shown that the orienting of attention follows a reliable pattern of facilitation and then inhibition following a peripheral cue. However, the literature lacks a high-resolution spatiotemporal map of this pattern. Moreover, the use of visual placeholders to highlight potential stimulus locations is inconsistent. This is puzzling, given attention's well-known predilection for objects. In this article, we remedy these outstanding issues with a large-scale investigation charting the spatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
3
25
2
Order By: Relevance
“…We then found that, contrary to the narrow allocation of presaccadic attention for a structured visual field, attention dynamically spread over space as a function of the delay between cue-offset and saccade onset. These effects are in contrast with a recent report in which the disappearance of a briefly presented cue, during a fixation task, lead to slower reaction times in detecting the presence of a flashed target on a black screen in the absence of placeholders (Taylor et al, 2015). Contrary to these effects, we observed an overall increase in sensitivity after the disappearance of the target.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We then found that, contrary to the narrow allocation of presaccadic attention for a structured visual field, attention dynamically spread over space as a function of the delay between cue-offset and saccade onset. These effects are in contrast with a recent report in which the disappearance of a briefly presented cue, during a fixation task, lead to slower reaction times in detecting the presence of a flashed target on a black screen in the absence of placeholders (Taylor et al, 2015). Contrary to these effects, we observed an overall increase in sensitivity after the disappearance of the target.…”
Section: Discussioncontrasting
confidence: 99%
“…In our view, this difference is principally due to the difficulty in drawing conclusions about the deployment of attention based on the use of reaction times to supra-threshold stimuli (Handy et al, 1996). Indeed, with or without visual placeholders, reaction time benefits have been shown to cover entire visual quadrants or even entire visual hemifields (Bennett & Pratt, 2001;Hughes & Zimba, 1987;Taylor et al, 2015). These results are in contradiction with the tight allocation of attention to a saccade target, or to an exogenous cue, observed through changes in visual sensitivity (Deubel & Schneider, 1996;Handy et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pratt, Sekuler and McAuliffe 34 suggested an influence of attentional set on early facilitation. Taylor, Chan, Bennet and Pratt 35 observed no facilitation and early IOR when potential target locations were not marked with placeholders. MacInnes 36 tested the spatial and temporal gradient of IOR with continuous random CTOAs and also found no early facilitation for either manual or saccadic responses.…”
Section: Introductionmentioning
confidence: 93%
“…While they generally seem to facilitate the attraction and alignment of attention, several researchers who have observed strong IOR in test conditions with placeholders failed to see that when the placeholders were removed (e.g., Birmingham & Pratt, 2005;Pratt & Chasteen, 2007;Jefferies & Di Lollo, 2015;Taylor, Chan, Bennett, & Pratt, 2015). Furthermore, while attentional facilitation seems to spread with a gradient-like profile from the center of a cue (Downing & Pinker, 1985;Shulman, Wilson, & Sheehy, 1985;Shulman, Sheehy, & Wilson, 1986)-preferentially within but also across framed objects (Egly et al, 1994;Nothdurft, 2016a)-the spread of inhibition appears to be blocked by placeholder frames (Taylor et al, 2015). As a matter of fact, even some of the early cuing experiments (which revealed attentional benefits and costs and, under certain circumstances, IOR; Posner & Cohen, 1984) used placeholder boxes which were eventually cued and in which the later targets were presented.…”
Section: Introductionmentioning
confidence: 99%